IDENTIFIKASI KARAKTERISTIK ORANG RISIKO TINGGI HIV DAN AIDS TENTANG PROGRAM PELAYANAN VOLUNTARY COUNSELING AND TESTING (VCT) - Husnul ' Umam; Yulia Irvani Dewi; Veny ' Elita (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Keperawatan, 2015)
Abstract The purpose of this research was to determine the characteristics of people with the high risk of HIV and AIDS on VCT service program. This research method was a quantitative description of the cross-sectional design. This research was conducted in Puskesmas Simpang Tiga. The sampling method was stratified sampling of respondents 84 people. Measuring instrument used was a questionnaire that has been tested for validity and reliability. The analysis used was a univariate analysis. The results showed that most respondents have good knowledge (53.6%), a positive perception (54.8%), a positive attitude (56%), and low motivation (59.5%) on HIV/AIDS and VCT service programs. The results of this research are expected to workers public of health, LKB cadres, and non government organization to increase the motivation to people with high risk of HIV and AIDS on VCT service programs to increase visiting on VCT services. Keywords : Characteristics of people with high risk of HIV and AIDS, VCT services